Long non-coding RNA SNHG16 regulates cell behaviors through miR-542-3p/HNF4α axis via RAS/RAF/MEK/ERK signaling pathway in pediatric neuroblastoma cells. Issue 5 (26th May 2020) - Deng, Defeng; Yang, Shuangjie; Wang, Xiang
Abstract: Neuroblastoma (NB) is an extracranial solid tumor in children with complex mechanism. Increasing reports indicated that long non-coding RNA (lncRNA) small nucleolar RNA host gene 16 (SNHG16) account for the pathogenesis of NB. Nevertheless, the precise functions of SNHG16 needed to be further exposed in NB progression. Our data revealed that SNHG16 and hepatocyte nuclear factor 4 α (HNF4α) were up-regulated, but miR-542-3p was down-regulated in NB. Knockdown of SNHG16 or HNF4α could impede cell proliferation, migration, invasion, and epithelial–mesenchymal transition (EMT) in vitro . Interestingly, the role of SNHG16 detetion in cell behaviors was rescued by HNF4α overexpression in NB cells. Mechanically, SNHG16 modulated the progression of tumor growth via miR-542-3p/HNF4α axis in NB. Also, SNHG16 knockdown inactivated rat sarcoma/effector of RAS/mitogen-activated extracellular signal-regulated kinase/extracellular regulated protein kinases (RAS/RAF/MEK/ERK) signaling pathway through HNF4α. Therefore, SNHG16/miR-542-3p/HNF4α axis modified NB progression via RAS/RAF/MEK/ERK signaling pathway, might highlight a novel therapeutic approach for NB.